2022
DOI: 10.21203/rs.3.rs-1462234/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Special Intrauterine Balloon and Intrauterine Contraceptive Device after TCRA in the Treatment of Intrauterine Adhesions

Abstract: Background It is of vital importance to focus on the prevention of intrauterine adhesion(IUA) relapse. Up to now, which method has a higher efficacy is still a matter of controversy. We tried to find a better method. Methods In this retrospective cohort study, all of the 69 included IUA patients experienced transcervical resection of adhesion(TCRA), and after surgery, 31 patients were placed special intrauterine balloon(IUB) and 38 patients were placed intrauterine contraception device(IUD). All IUA patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Studies on IND/Cu-IUDs have shown the same or better contraceptive efficacy as Cu-IUDs alone and significantly lower rates of removal for bleeding/pain and discontinuation. [41][42][43] Though overall bleeding patterns with Cu-IUDs and LNG-IUS differ markedly, the reduction of uterine bleeding through the addition of indomethacin to the LNG-IUS 8 device observed in our study is consistent with the beneficial impact on bleeding volume seen with IND/Cu-IUDs.…”
Section: Results In Context Of What Is Knownsupporting
confidence: 81%
“…Studies on IND/Cu-IUDs have shown the same or better contraceptive efficacy as Cu-IUDs alone and significantly lower rates of removal for bleeding/pain and discontinuation. [41][42][43] Though overall bleeding patterns with Cu-IUDs and LNG-IUS differ markedly, the reduction of uterine bleeding through the addition of indomethacin to the LNG-IUS 8 device observed in our study is consistent with the beneficial impact on bleeding volume seen with IND/Cu-IUDs.…”
Section: Results In Context Of What Is Knownsupporting
confidence: 81%